(untitled) (Journal of Pharmaceutical Negative Results, 2021)
Background: Ureteropelvic junction obstruction (UPJO) is defined as a condition whereby there is obstruction at the level of outlet where the ureter starts branching from the renal pelvis and this hinders the free flow of urine. Horseshoe kidney and ureteropelvic junction obstruction: congenital UPJ obstruction take place when there is an aperistaltic segment in the ureter. Objective: To identify the hypothesis of whether unilateral congenital UPJO can be effectively managed with open Anderson Hynes Pyeloplasty in children aged 5 to 16 years and examine the impact of the following on the rate of kidney function improvement: GFR, SRF, APD of renal pelvis, and changes in parenchymal thickness. Study design : A cross sectional retrospective study Place and duration of study. from June 2021 to December 2021 the Pediatric Urology Department, Institute of kidney diseases Peshawar. Methodology: The study design was a cross-sectional retrospective consecutive case series of an identifiable population of patients aged from 5-16 years with primary unilateral UPJO who underwent Anderson-Hynes dismembered pyeloplasty from June 2021 to December 2021 the Pediatric Urology Department, Institute of kidney diseases Peshawar. Pre- and post-operative records were matched and analyzed to determine the impacts it made on the alterations to GFR, SRF, APD of the renal pelvis and changes in the parenchymal thickness. Results: The follow-up investigations revealed that postoperative GFR and SFR measurement detected on DTPA renal scan three months after the operation was significantly higher than pre-surgery score. By the end of the third month follow up, the comparative analysis showed appreciable changes in the APD and parenchymal thickness, evaluated on ultrasound KUB. From a review of the literature, therefore, it is deduced that Anderson Hynes dutch dismembered pyeloplasty is a standard and efficient method in managing UPJO in children.